An Investigation of Dust Aerosols and Atmospheric Profiles Associated with North Atlantic Hurricanes Using Multi-Sensor Measurements - Kamal, Mohammed M. (2013)
MODerate resolution Imaging Spectroradiometer (MODIS) Aerosol Optical Thickness (AOT) and the Atmospheric Infrared Sounder (AIRS) atmospheric profiles (temperature and moisture) Level 2 products are studied to investigate dust aerosol impacts on hurricanes through spatial analysis for four hurricanes Isabel (2003), Frances (2004), Katrina (2005) and Helene (2006). Spatial regions were selected based on two concentric circles (an annulus) and segmented by left and right regions of 180° each around the hurricane's eye. Statistical relationships between MODIS AOT, AIRS temperature and percent relative humidity (RH) among these four hurricanes is presented. The variation of temperature and RH values represented in static-left, static-right, dynamic-left and dynamic-right for the 500 mb, 700 mb and 850 mb pressure levels were analyzed to determine the impacts of dust aerosols on temperature and RH. For the four hurricanes' average, AOT was found highest in Helene as opposed to (0.27) Isabel (0.23), Frances (0.18) and Katrina (0.16). Dust aerosols showed negative impacts on the atmospheric moisture levels and positive on the temperature.